Active Pointing Compensation of a HTS Multibeam Antenna - Xudong Wang; Pengpeng Wang (International Journal of Aerospace Engineering)
Active pointing compensation of a High Throughput Satellite (HTS) multibeam antenna via microfiber composites (MFCs) is studied in this paper. Electrical-mechanical coupling analysis of MFCs is conducted to quantitatively determine driving forces and moments of MFCs attached on a carbon fiber reinforced composite (CFRP) laminate, and a positive correlation relationship is observed for driving ability versus thickness of the laminate. By different driving strategies, MFCs could act in bending mode and torsioning mode for structural deformation control, and driving efficiency of the MFCs on a multibeam antenna is studied. Thermal distortion of the antenna under a typical in orbit thermal distribution causes the reflector to rotate about y axis with an pointing error of 0.005°, active compensation is conducted, and the final compensation results show that with an optimal voltage of 432 V, pointing error of the antenna is greatly compensated, and the depointing angle is corrected to be 0.00004°.